2010
DOI: 10.1021/jm9017866
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Selective Small-Molecule Melanocortin-4 Receptor Agonist with Efficacy in a Pilot Study of Sexual Dysfunction in Humans

Abstract: The relevance of the melanocortin system to sexual activity is well established, and nonselective peptide agonists of the melanocortin receptors have shown evidence of efficacy in human sexual dysfunction. The role of the MC4 receptor subtype has received particular scrutiny, but the sufficiency of its selective activation in potentiating sexual response has remained uncertain owing to conflicting data from studies in preclinical species. We describe here the discovery of a novel series of small-molecule MC4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
0
22
0
2
Order By: Relevance
“…However, a clinical trial in 2009 indicated potent side effects including an increase in blood pressure with the use of the peptide agonist LY2112688 (Ac-DArg-c[Cys-Glu-His-DPhe-Arg-Trp-Cys]-NH 2 ) [25] and decreased the rate of MC4R-selective small molecule agonist development as anti-obesity treatments. The potential uses of MC4R agonists as pro-erectile agents or MC4R antagonists as weight gain therapeutics for cachexia patients have also been investigated [137-139]. …”
Section: Small Molecule Ligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a clinical trial in 2009 indicated potent side effects including an increase in blood pressure with the use of the peptide agonist LY2112688 (Ac-DArg-c[Cys-Glu-His-DPhe-Arg-Trp-Cys]-NH 2 ) [25] and decreased the rate of MC4R-selective small molecule agonist development as anti-obesity treatments. The potential uses of MC4R agonists as pro-erectile agents or MC4R antagonists as weight gain therapeutics for cachexia patients have also been investigated [137-139]. …”
Section: Small Molecule Ligandsmentioning
confidence: 99%
“…( 13 , Figure 3) [137]. A previous MC4R agonist developed by this group possessing a 4-alcohol on the phenylpiperidine ring suggested small flanking substitutions on the C3 and C5 position of the piperidine ring had a beneficial effect, and was the basis for their structure-activity relation study.…”
Section: Small Molecule Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we investigated the effects of daily MTII and the more selective, small molecule MC4R agonist, PF446687 (Lansdell et al, 2010) injections during the first week of life on juvenile play and adult pair bonding in males and female prairie voles. We also assessed the impact of peripheral MTII on hypothalamic neuropeptide systems using the immediate early gene, early growth response factor-1, as a marker of neuronal activity.…”
Section: Introductionmentioning
confidence: 99%